Pioneering Interactive Learning: Enhancing Al-Istima' Skills in 10th Grade Madrasah Aliyah with iSpring Suite 9 Educational Media Development - Latief Nurjanah; Abdullah Ridlo (Language, Technology, and Social Media, 2023)
This study aims to develop interactive learning media utilizing iSpring Suite 9 to enhance maharah al-istima’ (listening comprehension) skills among 10th-grade students at Madrasah Aliyah (MA). The proposed media is designed to facilitate the Arabic language learning process by increasing student engagement and fostering an active learning environment. The research employs a development methodology based on Sugiyono’s seven-stage model, including problem identification, data collection, design, validation, revision, testing, and final product evaluation. Expert validation was conducted by two subject matter specialists and two design/media experts, with additional feedback from educators and students. The effectiveness of the media was further assessed through small-scale testing (n=15) and field trials (n=42) at MA Assyifa Karang Sari in South Lampung. The results demonstrate high feasibility, with ratings of 85% from subject matter experts (highly feasible), 92% from design/media experts (highly feasible), and 83% from both small-scale and field testing (very interesting). In conclusion, the interactive learning media developed using iSpring Suite 9 is deemed highly effective and suitable for enhancing listening comprehension skills in Arabic education, offering a practical and user-friendly solution for educators and students alike.